أساليب المعاملة الوالدية وعلاقتها بقلق المستقبل لدى تلاميذ السنة الثالثة ثانوي "دراسة ميدانية على عينة من طلبة ثانويتي مفدي زكريا وامحمد التجاني _ بالبياضة - هديل العبيد; جيهان بحري (جامعة الوادي - University of Eloued, 2025)
"هدفت هذه الدراسة للكشف عن العلاقة بين أساليب المعاملة الوالدية وقلق المستقبل لدى تلاميذ السنة الثالثة ثانوي، وقد أجريت الدراسة اعتمادا عن المنهج الوصفي بأساليبه (الارتباطي، الاستكشافي، والفارقي) حيث تم استخدام مقياس أساليب المعاملة الوالدية من إعداد (مرام راجح سليمان سمامرة، 2021) ومقياس قلق المستقبل (زقاوة أحمد، 2012) وطبقت الأداتان على عينة قوامها (200) تلميذ وتلميذة اختيروا بطريقة عرضية، من تلاميذ السنة الثالثة ثانوي بثانويتي مفدي زكريا وامحمد التجاني ولاية الوادي بالبياضة من الشعب التالية: آداب، علوم، تسيير. وتوصلت الدراسة إلى النتائج التالية: -وجود علاقة ارتباطية بين أساليب المعاملة الوالدية وقلق المستقبل لدى تلاميذ السنة الثالثة ثانوي. -عدم وجود فروق ذات دلالة إحصائية في أساليب المعاملة الوالدية لدى طلبة السنة ثالثة ثانوي تعزى لمتغير الجنس. -لا توجد فروق ذات دلالة إحصائية في درجة قلق المستقبل لدى طلبة السنة ثالثة ثانوي تعزى لمتغير الجنس. -توجد فروق ذات دلالة إحصائية في أساليب المعاملة الوالدية لدى طلبة السنة ثالثة ثانوي تعزى لمتغير الشعبة(تسيير). -لا توجد فروق ذات دلالة إحصائية في قلق المستقبل لدى طلبة السنة ثالثة ثانوي تعزى لمتغير الشعبة. "This study aimed to reveal the relationship between parental treatment methods and future anxiety among third-year secondary school students.the study was conducted using the descriptive approach with its correlational, exploratory,and comparative methods.the parental treatment styles scale, prepared by(MaramRajih Suleiman Samamra, 2021), and the future anxiety scal (Zaqawa Ahmed,2012) were used. The two tools were applied to a sample of (200) male and female students who where randomly selected from the third year secondary school students at Mufdi Zakaria and Amhamed Al-Tijani High Schools in El Bayadha, El Oued province, from the following streams: literature, sciences, and Management. The study reached the following results: - There is a correlational relationship between parental treatment styles and future anxiety among third-year secondary school students. - There are no statistically significant differences in parental treatment styles among third-year secondary school students attributable to gender. - There are no statistically significant differences in the degree of future anxiety among third-year secondary school students attributable to gender. - There are no statistically significant differences in parental treatment styles among third-year secondary school students attributed to the stream variable. - There are no statistically significant differences in future anxiety among third-year secondary school students attributed to the stream variable.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: طلبة السنة ثالثة ثانوي; قلق المستقبل; أساليب المعاملة الوالدية; Parenting styles; future anxiety; third-year secondary school students.